Mathematical Applications Of a Rough Topology In Medical Events (COVID19) (مجلة البحوث الأكاديمية, 2021)
This study aims to show that we can use the modern mathematics such as a rough topology to analyze many real life problems. The rough set theory is a good formal tool for processing incomplete information in an information system. The concepts of a rough topology based on the concepts of upper and lower approximations of a given set called universal. Rough set theory use in many areas. Here, we will apply this theory in a new medical event (COVID19). Our work us the rough topology to analyze many real life problems. Our result we try to find the good deciding factor   for the diseases COVID19..
Keywords: Rough Sets; Lower Approximation; Upper Approximation Rough Topology; Core